Active vibration control of smart laminated beams using PFRC patches as sensors and actuators. (2020) - Prakash, Bhanu; Amir, Mohammad; Yasin, M.Y.; Khan, A.H.
Abstract: The aim of this paper is to present the performance of piezoelectric fiber-reinforced composite (PFRC) sensors and actuators in active vibration suppression of smart laminated beams. Finite element based on an efficient layerwise theory has been selected for the kinematic modelling of smart beam. Both classical (CGVF) and optimal (LQR and LQG) feedback control systems are employed to actively suppress the vibration. The effects of fiber volume fraction and fiber direction of PFRC on the settling time, active damping ratios, peak tip deflection and peak control voltage are studied. The effectiveness of control strategies in terms of minimum control voltage for a given settling time is presented